2022
DOI: 10.3389/fnmol.2022.916249
|View full text |Cite
|
Sign up to set email alerts
|

Necrosulfonamide Alleviates Acute Brain Injury of Intracerebral Hemorrhage via Inhibiting Inflammation and Necroptosis

Abstract: ObjectiveIntracerebral hemorrhage (ICH) is the most lethal subtype of stroke, without effective treatment. Necrosulfonamide (NSA), a specific inhibitor for mixed lineage kinase domain-like protein, has been reported to exert neuroprotective effects in neurological diseases by ameliorating neuroinflammation and necroptosis. We hypothesized that NSA would alleviate acute brain injury and improve behavioral outcomes after ICH.Materials and MethodsMale adult C57BL/6 mice were assigned randomly into three groups. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…This study revealed more pMLKL + /TH + and pMLKL + /Ub + cells measured through histological data, and higher ubiquitylated pMLKL levels measured using co-immunoprecipitation assay in MPTP-intoxicated SN than in the control group, and the reversal effects of NSA exposure implied that repeated treatment with NSA hinders the cell death-inducing activity of MLKL in PD mice. Furthermore, our finding that NSA had no effect on the MPTP-induced increase in RIPK1 and RIPK3 protein levels corresponded to previous findings in rodent models 4 , 31 , indicating that NSA acts specifically on MLKL in vivo. NSA treatment reduced the MPTP-induced increase in MLKL protein levels in the MPTP mice.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study revealed more pMLKL + /TH + and pMLKL + /Ub + cells measured through histological data, and higher ubiquitylated pMLKL levels measured using co-immunoprecipitation assay in MPTP-intoxicated SN than in the control group, and the reversal effects of NSA exposure implied that repeated treatment with NSA hinders the cell death-inducing activity of MLKL in PD mice. Furthermore, our finding that NSA had no effect on the MPTP-induced increase in RIPK1 and RIPK3 protein levels corresponded to previous findings in rodent models 4 , 31 , indicating that NSA acts specifically on MLKL in vivo. NSA treatment reduced the MPTP-induced increase in MLKL protein levels in the MPTP mice.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, NSA exhibited neuroprotective effects after ischemic brain injury in mice by inducing MLKL ubiquitination and degradation 32 . Moreover, NSA alleviated acute brain injury in a mouse intracerebral hemorrhage model by inhibiting inflammation and necroptosis 4 . However, the potential effect of NSA on the pathophysiology of PD has not yet been reported.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, testing of the related caspase-1 inhibitor VX-740 was discontinued in a RA clinical trial due to the liver toxicity observed in animal models ( 295 ). Inhibiting GSDMD by necrosulfonamide reduces neuroinflammation and necroptosis in collagenase VII-induced mouse intracerebral hemorrhage model ( 277 ). In addition, dimethyl fumarate, an immunosuppressive drug used for the treatment of recurrent remission MS and plaque psoriasis promotes succination of GSDMD, which in turn disrupts the interaction with caspase-1 and blocks pyropotosis ( 278 ).…”
Section: Targeting Inflammasome Molecules To Prevent/treat Autoimmunitymentioning
confidence: 99%
“…1 Neuroinflammation and oxidative stress are involved in secondary brain injury after ICH, [2][3][4] and the extensive literature on these pathogenic mechanisms uncover new insights to counter the pathologic sequelae of ICH. At present, surgical or traditional treatments are still the main options, 5,6 broad pre-clinical studies have been completed, [7][8][9] and numerous researches are pouring in, [10][11][12] however, there is no widely recognized and effective method to ameliorate secondary brain injury 13 and improve the prognosis of ICH. 14 For example, applying hyperosmolar agents and external ventricular drain placement to cope with the decreased alertness caused by mass effect of ICH may be appropriate.…”
Section: Introductionmentioning
confidence: 99%